ABOUT INDICATORS OF PUBLIC HEALTH - Данцигер, Дмитрий Григорьевич; Филимонов, Сергей Николаевич; Андриевский, Борис Павлович; Часовников, Константин Викторович (Medicine in Kuzbass, 2022)
The purpose of this work is to substantiate the conceptual apparatus of public health through indicators of reproduction (birth, death) and morbidity. The article shows a set of health parameters that healthcare organizers (heads of medical organizations and institutions) should use. The methodology of the complex scientific discipline «operations research» [6] was used. A scheme for studying public health indicators, consisting of three main groups, is proposed.